The Test of Antibacterial Activity of Bangle Rhizome (Zingiber montanum) against the Growth of Streptococcus mutans, Porphyromonas gingivalis, and Enterococcus faecalis bacteria - Devi Indrian Ningsih; Mashhudi Mashhudi; Listiyawati Listiyawati (Jurnal Impresi Indonesia, 2024)
Various therapeutic agents can be used to help maintain a neutral condition in the oral cavity, one of which is mouthwash. However, mouthwash uses synthetic active chemical ingredients which, in the long term, may pose risks to health; in certain levels, it has been reported to cause side effects and is toxic. Bangle rhizome (Zingiber montanum) is a natural ingredient that contains various phytochemicals and has antibacterial properties. This research aims to observe the extent of inhibitory property of bangle rhizome against the growth of Streptococcus mutans, Porphyromonas gingivalis and Enterococcus faecalis. The ethanol extract of bangle rhizome was divided into 5 concentrations (60% w/v, 70% w/v, 80% w/v, 90% w/v, and 100% w/v). The inhibitory property test was performed using the Kirby-Bauer disk diffusion test with 3 replications. Chlorhexidine 0.2% was used as positive control and DMSO 10% was used as negative control. The results of this research showed that the ethanol extract of bangle rhizome could inhibit the growth of Streptococcus mutans, Porphyromonas gingivalis and Enterococcus faecalis bacteria in all concentrations.